Sitting in darkness Americans in the Philippines - Bain, David Haward (Boston Houghton Mifflin, 1984)
Tells the story behind two American military expeditions into the Philippines--the first in 1901 and the second in 1982--while examining American Filipino relations, past and present.
PART ONE: The City: 1. An American and His Country -- 2. Manila, 1982 -- 3. A FIlipino and His Country -- 4. Manila, 1901.

PART TWO: The Wilderness: 5. Dinalungan, Aurora Province, 1982 -- 6. Casiguran Sound, 1901 -- 7. From Casiguran to Casapsapan Bay, 1982 -- 8. The Odyssey to Palanan, 1899-1901 -- 9. From Dinapiqui to North of Dinatadmo Point, 1982 -- 10. Casiguran and the Contracosta, 1901 -- 11. On the Coast to Diguyo, 1982 -- 12. On the Way to Palanan, 1901 -- 13. On the Way to Palanan, 1982.

PART THREE: The Village: 14. Palanan, 1901 -- 15. Palanan, The End of the Trail.
Includes bibliographical references (pages 441-454) and index.
Keywords: Funston, Frederick -- 1865-1917.; Aguinaldo, Emilio -- 1869-1964.; Bain, David Haward; Philippines--History -- Philippine American War, 1899-1902.; Luzon -- Description and travel